ANALYSIS OF THE INFLUENCE OF JOB STRESS AND JOB SATISFACTION ON TURNOVER INTENTION AT SALES EMPLOYEE PT SINAR MUTIARA CAKRABUANA JAKARTA - Kurniawati, Widya; Haribowo, Putut; Saleh, Khairul (Admisi dan Bisnis, 2019)
This study aims to find out (1) the influence of job stress on turnover intention at PT Sinar Mutiara Cakrabuana, (2) The influence of job satisfaction on turnover intention at PT Sinar Mutiara Cakrabuana, and (3) The influence of job stress and job satisfaction on turnover intention at PT Sinar Mutiara Cakrabuana. The collecting data methods used in this study were interview, questionnaires, and literature studies. The scale of questionnaires used agree-disagree scale with 10 point scale. The sample in this study were 60 Sales employees of PT Sinar Mutiara Cakrabuana. The data analysis technique used was multiple linear regression. The results of multiple linear regression showed that job stress had a positive and significant influence on turnover intention, and job satisfaction had a negative and significant influence on turnover intention. Job stress and job satisfaction given contribute 30.4% to turnover intention. That means that 30.4% turnover intention was explained by job stress and job satisfaction, while 69.6% was explained by other factors not examined in this study.